PENGARUH CUSTOMER VALUE TERHADAP REPURCHASE INTENTION DENGAN GREEN MARKETING SEBAGAI PEMODERASI PADA STARBUCKS DI PAKUWON TRADE CENTER SURABAYA - Jocelin Leony Tjokro; Jason Widagdo; Moses Soediro; Fabiola Leoparjo (JURNAL ILMIAH EDUNOMIKA, 2025)
Using green marketing as a moderating variable, this study wants to find out how customer value affects Starbucks patrons' intentions to repurchase in Pakuwon Trade Center (PTC) in Surabaya. Data from 200 respondents who had bought Starbucks products at PTC Surabaya, were between the ages of 17 and 65, and were aware of the company's green marketing initiatives such as the use of eco-friendly packaging, sustainability promotions, or the Bring Your Own Tumbler program were collected quantitatively using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method. The findings show that repurchase intention is positively and significantly impacted by customer value and positively impacted by green marketing. Additionally, green marketing modifies the association between customer value and desire to repurchase, suggesting that eco-friendly marketing tactics enhance the impact of perceived value on consumers' intentions to make additional purchases. In the cutthroat food and beverage (F&B) sector, like Starbucks, these results demonstrate how crucial it is to combine green marketing tactics with consumer value to increase customer loyalty.